Comparative study of low temperature denitration performance of Mn-Ce/ACFA-TiO2 catalysts under oxy-fuel and air-fuel combustion flue gases - Xiang Gou; Ruiping Zhang; Guoyou Xu; Dong Zhao (Energy Reports, 2020)
Low temperature selective catalytic reduction (SCR) catalysts were prepared by using acetic acid modified fly ash (ACFA) and TiO2 with the loading of Mn-Ce. The powder catalysts were characterized by BET, XRD and SEM. The effects of Mn-Ce molar ratio on the NO conversion of SCR catalyst were investigated under different atmospheres of N2 and CO2, respectively. The 8% Mn-Ce/ACFA-TiO2 catalyst with Mn-Ce molar ratio of 1:1 showed good performance of NO conversion at 300~°C, 84.28% in N2 atmosphere and 74.29% in CO2 atmosphere. N2O was observed in the experiments of 8% Mn/ACFA-TiO2, 95.3 ppm in N2 atmosphere and 103.6 ppm in CO2atmosphere, respectively.
Keywords: 330; CO2 atmosphere; Low temperature SCR; Mn-Ce/ACFA-TiO; N2O formation; Oxy-fuel